Simulating X-ray spectroscopies and calculating core-excited states of molecules - Norman, Patrick; Dreuw, Andreas (Chemical reviews, 2018)
During the past decade, the research field of computational X-ray spectroscopy has witnessed an advancement triggered by the development of advanced synchrotron light sources and X-ray free electron lasers that in turn has enabled new sophisticated experiments with needs for supporting theoretical investigations. Following a discussion about fundamental conceptual aspects of the physical nature of core excitations and the concomitant requirements on theoretical methods, an overview is given of the major developments made in electronic-structure theory for the purpose of simulating advanced X-ray spectroscopies, covering methods based on density-functional theory as well as wave function theory. The capabilities of these theoretical approaches are illustrated by an overview of simulations of selected linear and nonlinear X-ray spectroscopies, including X-ray absorption spectroscopy (XAS), X-ray natural circular dichroism (XNCD), X-ray emission spectroscopy (XES), resonant inelastic X-ray scattering (RIXS), and X-ray two-photon absorption (XTPA)
Gesehen am 06.02.2020